Public Health and International Partnerships in the Democratic People’s Republic of Korea - Grundy, John; Biggs, Beverley-Ann; Hipgrave, David B. (PLOS Medicine, 2016)
David Hipgrave and colleagues argue that sustained collaboration is required to improve population health and health services in North Korea.